Analisis Pengaruh Konsentrasi Perekat Tepung Tapioka terhadap Pengurangan Kadar Abu pada Briket Tempurung Kelapa - Napitupulu, Robert; Pratama, Randa Julio; Dharta, Yuli (Politeknik Negeri Lhokseumawe, 2025)
Binder is a crucial component in briquette production, serving to consolidate charcoal particles into a solid form. This study aims to analyze the effect of tapioca starch concentration as a binder on the reduction of ash content in coconut shell briquettes. The binder concentrations used were 10%, 15%, and 20% of the total material mixture, with ash content testing conducted according to SNI 01-6235-2000 standards. The briquette production process included raw material preparation, mixing, molding, and drying. The results showed that binder concentration significantly affected the briquette's ash content. Lower binder concentrations resulted in reduced ash content, with the optimal ash content of 1.52% achieved at a 10% binder concentration. Excess binder tended to increase ash content due to residual binder that did not fully combust. These findings highlight the importance of controlling binder concentration to improve the quality of coconut shell briquettes as an alternative fuel source.